Multi-gene phylogeny and morphotaxonomy of Phaeosphaeria ampeli sp. nov. from Ficus ampelas and a new record of P. musae from Roystonea regia - Tennakoon, Danushka S.; Jeewon, Rajesh; Gentekaki, Eleni; Kuo, Chang-Hsin; Hyde, Kevin D. (Phytotaxa, 2019)
Phaeosphaeria ampeli is a new species collected from dead leaves of Ficus ampelas in Fanlu Township area, Dahu forest, Chiayi, Taiwan. Phaeosphaeria musae is a new record from dead leaves of Roystonea regia. Both species are described, illustrated and compared with similar species. Phaeosphaeria ampeli is distinguished from other Phaeosphaeria species based on distinct size differences of the ascomata, asci, ascospores and analyses of DNA sequence data. Maximum parsimony, maximum likelihood and Bayesian inference analyses of combined ITS, LSU, SSU and tef1-α sequence data are used to clarify the phylogenetic affinities of the species.